Investigating Post-translational Modifications in Neuropsychiatric Disease: The Next Frontier in Human Post-mortem Brain Research - Grubisha, Melanie J.; Sweet, Robert A.; MacDonald, Matthew L. (Frontiers in Molecular Neuroscience, 2021)
Gene expression and translation have been extensively studied in human postmortem brain tissue from subjects with psychiatric disease. Posttranslational modifications have received less attention despite their implication by unbiased genetic studies and importance in regulating neuronal and circuit function. Here we review the rationale for studying posttranslational modifications in psychiatric disease, recent findings in human postmortem tissue, the required controls for these types of studies, and highlight the emerging mass spectrometry approaches transforming this research direction.